Ethological Factors of Chronic Back Pain in MRI of a Group of Military Personnel - Saeed soleiman Meigooni; Shahnam baboli; Mohammad Hassan Kazemi-Galougahi; Negar Abdi; Meysam Mirzaie-Peyhani (مجله علمی دانشگاه علوم پزشکی کردستان, 2023)
Background and Aim: Chronic low back pain is one of the most common debilitating occupational diseases. It seems that the frequency of this type of back pain is increasing, especially among young military staff. The aim of this study was to evaluate the causes of chronic low back pain according to interpretation of MRI reports in military personnel of army land forces of the Islamic Republic of Iran. Materials and Methods: In this descriptive cross-sectional study, the data of military personnel with chronic low back pain, referring to the Neurosurgery Council of Khanevadeh Hospital, Tehran in 2016 were extracted. The information included demographic and occupational characteristics of the patients, clinical findings, and MRI reports. We used chi-square and Fischer exact tests for data analysis at the significance level of 95%. Results: 326 male military personnel with chronic low back pain were evaluated. The mean age of the subjects was 37.3 ± 0.6 years. The most common MRI finding was disc herniation which was detected in 174 cases (53.3%). low back pain was most frequent in the combat branch, which included 114 cases (34.9%). There was no statistically significant correlation between MRI findings and types of military branches (P=0.071). The highest frequency of disc herniation belonged to the patients between 20 and 29 years of age (p=0.002) and the highest frequency of degenerative changes was seen in the patients over 50 years of age (p=0.005). Conclusion: The most important finding of this study was the low mean age of the patients with chronic low back pain who were in their active working years. We suggest revision of the trend of periodic examinations of military personnel, ergonomics of the work environment and military training.